Oral nifedipine versus intravenous labetalol for acute blood pressure control in hypertensive emergencies of pregnancy: a randomized controlled trial - Alam, Anjuman; Zakaria, S. M. A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: To compare intravenous labetalol with oral nifedipine in terms of rapidity at which they control blood pressure in acute hypertensive emergencies of pregnancy. Methods: A randomized controlled study. Pregnant women with severe gestational hypertension with BP ≥160/110 mmHg after ≥20 weeks of gestation were randomized with computer generated numbers, either to receive IV labetalol with an escalating dose of 20, 40, 80, 80 and 80 mg or nifedipine capsule orally in a dose of 10 mg every 15 minutes (upto 5 doses) until a BP of ≤150/100 mmHg is achieved. Crossover treatment was to be effected if initial treatment regimen was unsuccessful. Primary outcome was time taken and number of doses required to achieve the target BP of ≤150/100 mmHg. Secondary outcomes were volume of urine output, maternal heart rate changes, fetal heart rate abnormality, perinatal and maternal outcome and side effects. Results: Oral nifedipine achieved the target BP (≤150/100 mmHg) more rapidly in (26.25±12.60) minutes in comparison to (32.62±12.19) minutes with IV labetalol (p= 0.024). Nifedipine group also took less number of doses to achieve the target BP of (≤150/100 mmHg) mmHg than IV labetalol (1.75±0.840 vs. 2.18±0.83), p= 0.024. Volume of urine output was also significantly more in nifedipine group (94.90±1.84 ml) at 1 hour and thereafter till 24 hour of treatment in comparison to IV labetalol (41.28±2.14 ml), p= 0.000. Side effects are few and not serious. No patient required crossover treatment. Conclusions: Both the drugs are equally effective in controlling acute hypertensive emergencies of pregnancy, however oral nifedipine is more rapid in controlling severe hypertension and also it is associated with significantly increased urine output.